Giving an Academic Presentation in English Intermediate Level - Wallwork, Adrian (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is for university students, with at least a mid-intermediate level of English. It can be used as part of an English for Academic Purposes (EAP) course, either alone or with the companion volume Writing an Academic Paper in English. The chapters are independent so that EAP teachers and students can choose those sections that best fit their needs. This means that a course could range from a minimum of 20 hours, up to 60 hours or more. There is an introductory chapter that includes what role academics play in today's world, where success is not just measured in terms of paper output and presentations at conferences, but also in involvement interdisciplinary projects and supporting society at large. Each chapter covers either a particular skill (e.g. preparing a script, pronunciation, visuals, how to begin and end a presentation) or the particular purpose of a specific moment in a presentation. For example, the final slide is designed not just to conclude and thank the audience, but is an opportunity to reach out for collaborations and assistance. The aims of each part of a presentation are also highlighted by comparisons with non-academic situations where similar skills are required. The course is highly practical with screenshots from real presentations given by PhD students. It is also designed to be fun to use. Other books in the series: Writing an Academic Paper in English Essential English Grammar and Communication Strategies Adrian Wallwork is the author of more than 40 ELT and EAP textbooks. He has trained several thousand PhD students and researchers from around 50 countries to write research papers and give presentations. He is also the co-founder of e4ac.com, an editing agency for non-native English-speaking researchers.
Chapter 1 The key aims of a presentation -- Chapter 2 Resources: Presentations on TED and YouTube -- Chapter 3 Preparing a script before you create the slides -- Chapter 4 Pronunciation, intonation, and speed of voice -- Chapter 5 Titles -- Chapter 6 Starting your presentation: giving the big picture -- Chapter 7 Agenda -- Chapter 8 Explaining technical slides -- Chapter 9 The visual aspect of slides -- Chapter 10 The conclusions and final slide -- Chapter 11 Q&A session -- Chapter 12 Doing presentations online -- Chapter 13 Practising, improving, and getting feedback.
Keywords: Linguistics; Language and languages-Study and teaching; Linguistics; Language Education; Theoretical Linguistics / Grammar